Kāndamn̄œnngān ph̄ưa t̨ōpsan̨ōng khwāmt̨ōngkān kānrīanrū khan ph̄ưnthān patinyā lōk wādūai kānsưksā ph̄ưa pūangchon læ kr̨ōp - Thipphawan Bunchūai; Wanthanī Thaithīang; Ph̨̄onthip Kānčhananiyot (Thailand Substance Committee in preparation for the WCEFA 1990, 1990)
World declaration on education for all and framework for action to meet basic learning needs adopted by the World Conference on Education for All : Meeting Basic Learning Needs, Jomtien, Thailand, 5-9 March 1990.